Peraturan Daerah Syariah dalam Bingkai Otonomi Daerah - Bik, Alwi (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Abstract: The authority in making the Regional Regulation (Perda) is a tangible manifestation of the application of the widely autonomy owned by a certain region. As a country that adheres to the principle of legality in each preparation and formation of legislation, the definition of regional authority in the preparation and establishment of local regulations must refer to the existing statutory provisions, especially those which govern the relationship between the central and the region in the Unitary of the Republic of Indonesia. Study on the existence of the Syariâah Regional Regulation is a topic of the discussion that characterizes the dynamics of science, especially after the reform in Indonesia. The standpoint of most of the discussions about the existence of the Syariâah Regional Regulation is quite varied, among others are: (a) from a legal standpoint,Â  namely Law No. 10 year 2004 aboutÂ  the establishment of laws and regulations; (b) from a political standpoint; (c) from a social standpoint, and; (d) assessment of the investment point of view. From some of these studies, public policy should be any more emphasis on the benefit aspects of society. It is based on the legal maxim âpolicy of a top leader to his people always leads to a benefitâ.Keywords: Regional regulation, shariâah, regional autonomy